PENGEMBANGAN UMKM WEDANG UWUH â€œMBAK DUKâ€ DI DESA MANGUNAN, BANTUL, YOGYAKARTA - Yessi Jusman; M.Thariq Assary; Henny febriani; Dea Anisya; M. Alfadha Tumahadi (Jurnal Pengabdian Masyarakat Multidisiplin, 2022)
Wedang uwuh was officially registered in the intangible cultural heritage in 2017. Wedang uwuh "mbak duk" efforts must be made to improve the quality of production and more modern marketing methods. This research was conducted using FGD and Mentoring/Coaching methods. The results of the research were the creation of a mini studio which was used for product photos, packaging changes and the giving of the wedang uwuh "mbak duk" logo on the packaging as product branding and the creation of an online media platform used for marketing activities. This activity is carried out periodically to foster and assist MSME partners to successfully use and utilize social media and market places to develop MSME product sales.